(untitled) (Pragnya Sarathi, 2026)
This paper is based on the results of the Mahji people’s fishing practices and their tools. Fishing is the act of catching fish. It is significant practices that ensure food security by providing a primary source of protein and sustaining the livelihood of marginalized communities. The study examined fishing gear, materials, and trapping methods used by minor communities along the Kaligandaki River near Maldhunga, Parbat District. A qualitative field survey method was used. Nine people from the Majhi community participated. Nets are dominant fishing implements, followed by Tiryari and bamboo baskets. Thali, hammering devices, umbrella traps, and Kudelo are used depending on fishing conditions. The Majhi people are inclined to the hybridization of modern and traditional resources. Local craftsmanship and skill-based production are used in fishing operations. Finding highlights of fishing practices in the area represents a transitional system in which modernization coexists with indigenous knowledge. The indigenous knowledge of fishing was observed in the field. Besides this, these practices are in crisis due to livelihood and lack of support.